Dimensional Stability of Lightweight Foamed Concrete Containing Eggshell Powder and Calcium Stearate - Tiong, Hock Yong; Lim, Siong Kang; Lee, Yee Ling (International Journal of Integrated Engineering, 2022)
In order to reduce eggshell (ES) waste and reduce utilization of pure cement, various researches were conducted to study effects of eggshell powder (ESP) on properties of concrete when it partially replaces ordinary Portland cement (OPC). Dimensional stability is one of the properties that related to cracking issue and soundness of concrete, and it is generally guided by movement of moisture. This study was conducted to study the sorptivity, initial surface absorption, and dimensional stability of lightweight foamed concrete (LFC) that containing eggshell powder and calcium stearate (CS), where, replacement level (RL) of eggshell powder ranged from 0% to 10% at interval of 2.5%, and additional of 1% calcium stearate as cement mass applied for the mixture containing 0% and 5% eggshell powder. The result shows that eggshell powder improves sorptivity, initial surface absorption, and dimensional stability of lightweight foamed concrete and the optimal replacement level is 5%. The result also shows that calcium stearate significantly improves these properties, regardless that incorporation of eggshell powder in the mixture containing calcium stearate might slightly deteriorate these properties. Besides, based on the results, improved sorptivity and initial surface absorption result in increased magnitude of shrinkage as the specimen has lower ability to absorb water for expansion throughout the testing period.